Corticosteroids and Intravenous Immunoglobulin in Pediatric Myocarditis: A Meta-Analysis - Li, Yining; Yu, Yuqing; Chen, Selena; Liao, Ying; Du, Junbao (Frontiers in Pediatrics, 2019)
Background: The efficacy of corticosteroids and intravenous immunoglobulin (IVIG) in pediatric myocarditis remains controversial. Objectives: The authors performed a meta-analysis to assess the therapeutic efficacy of corticosteroids and IVIG in children with myocarditis. Methods: We retrieved the trials on corticosteroids and IVIG therapy respectively in pediatric myocarditis from nine databases up to December 2018. Statistical analysis was performed using Review Manager 5.3. Results: Our analysis included 8 studies and 334 pediatric patients. The data demonstrated that children receiving corticosteroids showed no significant improvement on left ventricular ejection fraction (LVEF) from a one month- to eight month-follow-up (MD=5.17%, 95%CI=-0.26%-10.60%, P=0.06), and no significant improvement in death or heart transplantation incidence at the end of follow-up (OR=1.33, 95%CI=0.27-6.70, P=0.73). However, children receiving IVIG revealed a statistically remarkable increase in LVEF at a follow-up over the course of six months to one year (MD=18.91%, 95%CI=11.74%-26.08%, P<0.00001), and a decrease in death or heart transplantation at the end of follow-up (OR=0.31, 95%CI=0.12-0.75, P=0.01). Further comparisons showed that the mortality and heart transplantation rate of children with myocarditis treated with IVIG were significantly lower than those with corticosteroid therapy (t’=11.336, P<0.001). Conclusions: IVIG might be beneficial to improve LVEF and survival for myocarditis in children. However, the present evidence does not support corticosteroids as superior to conventional therapy in children with myocarditis. Further randomized controlled trials with a larger sample size are required.